Risk Factors of Sleep Quality in the Incidence of Burnouts Syndrome: An Analytical Observational Study of Medical Education Students - Dicky Timoti Tantono; Rizkie Woro Hastuti; Anita Soraya Soetoko (Journal of Advanced Multidisciplinary Research, 2023)
Burnout syndrome is a condition caused by long-term job stress. Poor sleep quality can have a negative impact on cognitive function, and emotional control which can increase the risk of developing burnout syndrome. This study aims to determine whether there are risk factors for sleep quality in the incidence of burnout syndrome among medical students. An observational study with a cross-sectional design was conducted with 157 medical students at the Sultan Agung Islamic University, Semarang. Data collection was carried out using the Maslach Burnout Inventory - Student Survey and the Pittsburgh Sleep Quality Index which assessed both variables within 1 month. The test used the frequency distribution and prevalence ratio test with a confidence interval (CI) of 95% (Î±=0.05). The prevalence of poor sleep quality and burnout syndrome is 73.2% and 21%. The results of the analysis using prevalence ratio calculations showed that there was an increased risk of burnout syndrome due to poor sleep quality by 3.6 times with a 95% confidence interval of 1.176-11.340. From these results it can be concluded that students with poor sleep quality are 3.65 times more likely to experience burnout syndrome than those with good sleep quality.